Interaction between polymorphisms of the oxytocinergic system genes and emotion perception in inpatients with anorexia nervosa. (5th August 2019) - Kucharska, Katarzyna; Kot, Emilia; Biernacka, Katarzyna; Zimowski, Janusz; Rogoza, Radosław; Rybakowski, Filip; Kostecka, Barbara; Bednarska‐Makaruk, Małgorzata
Abstract: Objective: The empirical literature describes the role of the oxytocinergic system in emotion perception (EP). Variants in the oxytocin (OXT) and oxytocin receptor genes have been associated with mental disorders, including anorexia nervosa (AN), that are characterized by difficulties in socioemotional functioning. Our study aimed to examine whether variability within the genes related to OXT pathways may play a role in facial EP in inpatients with AN. Method: Single nucleotide polymorphisms (SNPs) of the following genes: oxytocin receptor (rs2254298, rs53576), OXT (rs6133010), OXT‐arginine‐vasopressin (rs2740204), CD38 (rs6449197, rs3796863), and human leucyl/cystinylaminopeptidase (rs4869317) were genotyped in 60 AN female inpatients and 60 healthy control females (HCs). Associations between genetic polymorphisms and EP as well as clinical symptoms were examined. Results: The AN group showed decreased EP abilities compared with HCs. SNPs of rs2740204, rs6133010, and rs53576 were associated with differences in EP in women with AN and in HCs. The SNP of rs4869317 was associated with the level of eating disorders symptoms in HCs. Conclusions: The OXT system may be involved in EP difficulties in AN. SNPs within genes related to OXT pathways may influence EP abilities. The leucyl/cystinylaminopeptidase rs4869317 SNP may be involved in the development of eating disorders psychopathology.